Urban Public Perceptions and Usage of the 'Wira-Wiri Suroboyo' Feeder: Insights from the Theory of Planned Behavior - Pamula, Gisela Geraldine; Christy, Hilary; Syahnufi, Chiara Hanifah; Natalia, Johanna; Sampe Tondok, Marselius (Psychological Research on Urban Society, 2025)
Traffic congestion is a major transportation issue in Surabaya, prompting the city government to introduce solutions such as the "Wira-Wiri Suroboyo" feeder service. While the Theory of Planned Behavior (TPB) has been widely used to explain public transportation use, it has not yet been applied to this context. To fill this lacuna, this study used TPB to explore the public perceptions of the Surabaya to use or not using the "Wira-Wiri Suroboyo" feeder. A qualitative approach was used with six purposively selected participants. Data were gathered through interviews and analyzed using interactive techniques. The research findings indicate that the reasons for using or not using the "Wira-Wiri Suroboyo" feeder are significantly influenced by positive or negative evaluations of the feeder, the influence of significant others, and the perceived ease or difficulty of accessing the "Wira-Wiri Suroboyo" feeder. The participants recommended improvements, such as expanding routes, adjusting schedules, enhancing app use, and improving infrastructure and facilities. These insights can help the government improve the effectiveness of the service and contribute to easing traffic congestion.